The role of serological tests and biopsy in the diagnosis of celiac disease: retrospective review of 1137 duodenal biopsies - Gurlek, Feridun; Tasdemir, Eyyup; Erkinuresin, Taskın (International Journal of Research in Medical Sciences, 2020)
Background: The aim of this study is to evaluate gluten sensitivity and/or celiac disease (CD) on the basis of serological tests and duodenal biopsy and to draw attention to the prevalence in the population and the correlation between serological tests and biopsy results. Methods: Patients who applied to Health Sciences University Bursa High Specialization Training and Research Hospital between 2015-2019 and who underwent serological tests and duodenal biopsies with a diagnosis of CD or gluten sensitivity were retrospectively analyzed. Results: The study was conducted with a total of 1137 cases, 61.2% (n = 696) of who were women and 38.8% (n = 441) were men. Their ages range from 17 to 91, with a mean of 40.16 ± 16.18 years. Of the 178 patients with gluten sensitivity, 122 (68%) were female and 56 (32%) were male. According to the results of duodenal biopsy, an average of 8% Marsh 3, 5% Marsh 1-2 was detected in the last five years. For the whole study, a significant difference was found between celiac autoantibody positivity rates according to the biopsy results (p = 0.001; p <0.01). The rate of serological test positivity was higher in patients with biopsy result Marsh 3 than those with normal biopsy result, peptic duodenitis and Marsh 1 and 2. No statistically significant difference was found between the rates of Marsh 3 biopsy results and serological test positivity by years (p> 0.05). Conclusions: The number of patients applied with a diagnosis of CD in the last five years has gradually increased (3.4-33.7%). Of the patients with Marsh 3 and Marsh 1-2 biopsy results, 78% were under 50 years old. This suggests that gluten enteropathy in young female patients having digestive system complaints should not be ignored during the diagnosis. Serological test results were highly correlated with the biopsy results in patients with Marsh 3 biopsy results. We think that if clinical findings are supported with serological tests and directed for biopsy in the diagnosis of celiac disease, it will be more cost effective and the workload and time loss will be prevented.